2016
DOI: 10.1039/c5cp05519a
|View full text |Cite
|
Sign up to set email alerts
|

I. Dissociation free energies of drug–receptor systems via non-equilibrium alchemical simulations: a theoretical framework

Abstract: In this contribution I critically revise the alchemical reversible approach in the context of the statistical mechanics theory of non covalent bonding in drug receptor systems. I show that most of the pitfalls and entanglements for the binding free energies evaluation in computer simulations are rooted in the equilibrium assumption that is implicit in the reversible method. These critical issues can be resolved by using a non-equilibrium variant of the alchemical method in molecular dynamics simulations, relyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 71 publications
(335 reference statements)
0
57
0
Order By: Relevance
“…The SMD with JI or CE for reweighting is widely applied to construct the PMF along a selected RC . The nonequilibrium trajectories are initiated from equilibrated structures sampled from the initial state ensemble and the initial configurations are pulled to the quasi‐equilibrium or nonequilibrium end state ensemble over a period of time with some external forces.…”
Section: Introductionmentioning
confidence: 99%
“…The SMD with JI or CE for reweighting is widely applied to construct the PMF along a selected RC . The nonequilibrium trajectories are initiated from equilibrated structures sampled from the initial state ensemble and the initial configurations are pulled to the quasi‐equilibrium or nonequilibrium end state ensemble over a period of time with some external forces.…”
Section: Introductionmentioning
confidence: 99%
“…When a method uses multiple models (e.g., MM is used to generate the conformations to evaluate at the QM level in DFT(TPSS)-D3), only the energy and solvation models used for the final free energy prediction are listed. COSMO-RS: conductor-like screening model for real solvents [61]; DDM: double decoupling method [39]; FM: Force Matching [28]; FSDAM: Fast switching double annihilation method [92,97] KMTISM: KECSA-Movable Type Implicit Solvation Model [131]; MD: molecular dynamics; MovTyp Movable Type method [130]; PBSA: Poisson-Boltzmann surface area [106]; REST: replica exchange with solute torsional tempering [68,71]; RFEC: relative free energy calculation; QM/MM: mixed quantum mechanics and molecular mechanics; SOMD: double annihilation or decoupling method performed with Sire/OpenMM6. Challenge entries generally performed better on OA/TEMOA than CB8 341 In general, the CB8 guest set proved to be more challenging than the OA/TEMOA set both in terms of error 342 and correlation statistics.…”
mentioning
confidence: 99%
“…These good performances of the NEW approach have been confirmed in the second round of the SAMPL6 challenge for the LogP. 21 In spite of the fact that the rare applications of NEW methods have been quite successfully for solvation and binding free energies of complex molecular systems, [32][33][34][35][36][37][38][39] the vast majority of practitioners still rely upon FEP-based technology, in most cases systematically and incautiously underrating the sampling issue. 26 This is probably due to incomplete or far-stretched analysis studies 31,40 where NEW methods have been shown, in specific examples, to be computationally comparable to or less efficient than equilibrium approaches.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the fact that NEW methods have been already applied quite successfully to solvation free energies 33,34 as well to drug-receptor [35][36][37] , host-guest 38,39 and even protein-protein 32 binding free energies, the vast majority of practitioners still stick to FEP-based technology. In the recent LogP/SAMPL6 challenge, NEW was used only in my submissions.…”
Section: Introductionmentioning
confidence: 99%